Exon skipping in Duchenne Muscle dystrophy due to a silent p.Ser443= mutation in the DMD gene. (June 2020) - Raj Joshi, Pushpa; Sarangerel, Jambal; Munkhbayar, Rentsenbat; Gläser, Dieter; Zierz, Stephan
Highlights: Identification of a rare silent pathogenic mutation in the DMD gene. cDNA investigation helpful in analyzing pathogenicity of silent mutations. The p.Ser443 = mutation extends the genetic spectrum in Duchenne Muscle dystrophy. Abstract: Duchenne Muscle dystrophy (DMD) is a X-linked inherited disease predominantly caused by severe mutations in DMD gene leading to absence of dystrophin protein. Here we report a 14-year-old Mongolian boy suffering from proximal muscle weakness, pseudohypertrophic deltoid and gastrocnemius muscles since early childhood. Lactate dehydrogenase (LDH) and creatine kinase (CK) levels were elevated. Mutation analysis including MLPA and sequencing of the DMD gene revealed a hemizygous silent variant, c.1329C>T (p.Ser443=) in exon 11. This silent mutation, listed in the SNP database (rs1060502631), was described as a variant of unknown significance (VUS) in ClinVar database. cDNA analysis demonstrated partial skipping of exon 11 due to this mutation. Although silent mutations are usually considered non-pathogenic, our case emphasizes that silent mutations can be potentially pathogenic. Hence, if silent variants are not annotated in database or not known to be benign, they should be analysed further at cDNA level.